Role of lipid-mobilising factor (LMF) in protecting tumour cells from oxidative damage - Sanders, P M (Nature Publishing Group, 2004)
Lipid-mobilising factor (LMF) is produced by cachexia-inducing tumours and is involved in the degradation of adipose tissue, with increased oxidation of the released fatty acids through an induction of uncoupling protein (UCP) expression. Since UCP-2 is thought to be involved in the detoxification of free radicals if LMF induced UCP-2 expression in tumour cells, it might attenuate free radical toxicity. As a model system we have used MAC13 tumour cells, which do not produce LMF. Addition of LMF caused a concentration-dependent increase in UCP-2 expression, as determined by immunoblotting. This effect was attenuated by the β3 antagonist SR59230A, suggesting that it was mediated through a β3 adrenoreceptor. Co-incubation of LMF with MAC13 cells reduced the growth-inhibitory effects of bleomycin, paraquat and hydrogen peroxide, known to be free radical generators, but not chlorambucil, an alkylating agent. There was no effect of LMF alone on cellular proliferation. These results indicate that LMF antagonises the antiproliferative effect of agents working through a free radical mechanism, and may partly explain the unresponsiveness to the chemotherapy of cachexia-inducing tumours.